Pengolahan Kelapa Menjadi Virgin Coconut Oil dengan Teknik Fermentasi di Desa Karanglayung - Maman Sudirman; Angga Sucitra Hendrayana; Enceng Enceng; Zulham Adamy (Universitas Pahlawan Tuanku Tambusai, 2023)
Fermentation is one of the techniques for making Virgin Coconut Oil (VCO) which is not widely known by the public. This technique has advantages over other methods because it is easy to do, inexpensive, and produces clear oil. However, the people of Karanglayung village are unfamiliar with the fermentation technique for making VCO. However, Karanglayung village has great potential for coconut plantations. Because of this, it is necessary to hold VCO processing training to improve the economic level of the community. Community Service Activities are carried out through three main stages: preparation, implementation, and evaluation. The community obtained information, benefits, and direct skills in processing VCO with fermentation techniques from this activity. VCO produced by participants had the largest volume of 276 mL with clear quality but sour smell. The evaluation showed that participants were satisfied with the activities, the lecture material, and feedback on questions asked during the activity. Besides being satisfied, 74% of participants are also interested in establishing their own VCO business.